Pengaruh Disiplin Kerja dan Loyalitas Kerja Terhadap Kinerja Karyawan PT Tiki Jalur Nugraha Ekakurir Cabang Cilegon - Putra, Rizki Septian; Sandra, Mela (Jurnal ATAMA, 2023)
This study intends to determine the effect of work discipline and work loyalty on employee performance; where the authors conducted research at PT Tiki Jalan Nugraha Ekakurir Cilegon Branch. The method used is quantitative, used to examine a particular population or sample, and the instrument used is a questionnaire. The total population in this study was 149 people who were the total employees of PT Tiki Lane Nugraha Ekakurir Cilegon Branch, and the sampling technique used was the Slovin formula with a total sample of 60 employees of PT Tiki Lane Nugraha Ekakurir Cilegon Branch. The study's results, partially work discipline obtained a t count of 2.205 > t table 2.664; thus, work discipline has no significant effect on employee performance. For the partial test of work loyalty obtained, t count 6.773 > t table = 2.664; thus, there is a significant influence between work discipline on employee performance. For the simultaneous f test or togetherness test, many F count 31.630 > F table 3.15 means a simultaneous influence between work discipline and work loyalty on employee performance. From the test results and the results of the multiple correlation analysis of the effect of work discipline and work loyalty on employee performance, the value received is 0.315, which means the relationship is moderate.